Influence of parafunctional loading and prosthetic connection on stress distribution: A 3D finite element analysis - Torcato, Leonardo Bueno [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Verri, Fellippo Ramos [UNESP]; Falcon-Antenucci, Rosse Mary [UNESP]; Santiago Júnior, Joel Ferreira [UNESP]; Faria Almeida, Daniel Augusto de [UNESP] (Elsevier B.V., 2015)
Statement of problem. Clinicians should consider parafunctional occlusal load when planning treatment. Prosthetic connections can reduce the stress distribution implant-supported prosthesis. Purpose. The purpose of this 3-dimensional finite element study was to parafunctional loading and prosthetic connections on stress distribution. Material and methods. Computer-aided design software was used to construct 3 models. Each model was composed of a bone and an implant (external hexagon, internal hexagon, or Morse taper) with a crown. Finite element analysis software was used to generate the finite element mesh and establish the loading and boundary conditions. A normal force (200-N axial load and 100-N oblique load) and parafunctional force (1000-N axial and 500-N oblique load) were applied. Results were visualized as the maximum principal stress. Three-way analysis of variance and Tukey test were performed, and the percentage of contribution of each variable to the stress concentration was calculated from sum-of squares-analysis. Results. Stress was concentrated around the implant at the cortical bone, and models with the external hexagonal implant showed the highest stresses (P<.001). Oblique loads produced high tensile stress concentrations on the site opposite the load direction. Conclusions. Internal connection implants presented the most favorable biomechanical situation, whereas the least favorable situation was the biomechanical behavior of external connection implants. Parafunctional loading increased the magnitude of stress by 3 to 4 times.